ANALISIS FINTECH LENDING SEBAGAI ALTERNATIF SUMBER PENDANAAN UNTUK MENGOPTIMALKAN PEMASUKAN BISNIS KECIL (UMKM) - Utama, Ahmad Nur Budi; Husain, Anggriani; Piola, Marina Paramitha Sari; Al-Amin, Al-Amin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Indonesia has experienced rapid economic growth, especially in the SME (Small and Medium Enterprises) sector. However, this growth is often hampered by limited access to capital and financing. As a solution, Fintech Lending has emerged as an innovative alternative source of funding. This study aims to analyze the role of Fintech Lending in supporting the optimization of income for small businesses in Indonesia. The method used is qualitative analysis with a literature study approach, involving data collection from various reliable and relevant sources. Research findings indicate that Fintech Lending provides ease of access to funding with a faster process and more flexible requirements compared to traditional financial institutions. This allows small business owners to expand operations, innovate, and ultimately optimize their business income. In addition, the transparency and fair credit assessment mechanisms of Fintech Lending help to build trust among small business players. Nonetheless, regulatory challenges and credit risks need to be considered to ensure the sustainability of this funding model. This research provides insights for stakeholders about the importance of integrating financial innovation and adequate regulatory support to advance the SME sector in Indonesia.